Analysis of the Social Dimension in the Interactions in the UNED Hosting Forums and Its Implications for the Design of a Chatbot for Educational Guidance - Guerrero-Bocanegra, Borja (2023)
Objective. To analyze the presence of the social dimension in the interactions of the hosting forums for new students at the UNED and to determine its implications in the design of a chatbot for initial educational guidance. Methodology. The presence of the social dimension in the interactions that took place in the virtual induction forums during the 2019/2020 academic year was analyzed and codified, specifically in the technical support forum, the orientation forum, and the mentoring forum in five of the degrees offered by the institution. The sample consisted of 1,461 messages sent through 12 virtual forums by a total of 570 people, to which the categorization proposed by Rourke et al. (1999) was applied deductively. Analysis of results. The data were processed with the help of computer-assisted qualitative data analysis software. Conclusions. It would be advisable for the initial educational guidance chatbot to show affect by expressing emotions, to be interactive by explicitly referring to the messages sent by the users, and to be cohesive by including greetings, encouragement, and vocatives.